Characterization of Adrenoceptors in the Guinea-Pig Pulmonary Artery (Journal of Science and Technology, 2015)
An investigation was carried out to determine the adrenoceptor types in isolated places of the guinea-pig pulmonary artery. The results indicated a predominance of α-adrenoceptors and the presence of a paucity of β- adrenoceptors in the tissue which may increase at the level of the pulmonary arterioies. The eympathomimetics used acted principally on the of α-adrenoceptors to produce contraction of the preparation.